2015
DOI: 10.1542/peds.2014-3652
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Request Process and Outcomes in Adult and Pediatric Organ Donation

Abstract: BACKGROUND AND OBJECTIVES: Although existing studies suggest that factors affecting families' decisions regarding pediatric organ donation mirror those for adult patients, health professionals working in this area maintain that pediatric and adult decision-makers differ in significant ways. This study compared the request process, experiences, and authorization decisions between family decision-makers (FDMs) of adult and pediatric donors and nondonors.METHODS: Perceptions of the donation request were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…To recruit family decision makers (FDMs), a validated contact and interview protocol was employed. (1821) FDMs were mailed recruitment packets two months after the organ donation approach (3 months for families of pediatric patients). Of the 2,232 individuals contacted, 1,601 (71.7%) FDMs agreed to be interviewed; 1,254 (78.3%) were FDMs of DBD patients; and 347 (21.7%) were FDMs of potential DCD patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To recruit family decision makers (FDMs), a validated contact and interview protocol was employed. (1821) FDMs were mailed recruitment packets two months after the organ donation approach (3 months for families of pediatric patients). Of the 2,232 individuals contacted, 1,601 (71.7%) FDMs agreed to be interviewed; 1,254 (78.3%) were FDMs of DBD patients; and 347 (21.7%) were FDMs of potential DCD patients.…”
Section: Methodsmentioning
confidence: 99%
“…Semi-structured telephone interviews, which have been validated for use with this population in previous studies,(1821) were conducted with participating families of donor-eligible patients. The interviews collected FDMs’ sociodemographic data, attitudes and knowledge about donation, assessment of the quality and content of the donation discussions held at the hospital, final donation decisions ( authorized/refused ), and reasons for that decision.…”
Section: Methodsmentioning
confidence: 99%
“…Consent for OD is almost exclusively provided by next of kin or appointed guardian. Decision makers for both adults and children consent relatively equally and the depth and detail of the donation discussion is associated with higher consent rates . Consent rates in Europe, North America, the UK and Australia for both adults and children range from 42 to 69% .…”
Section: Consentmentioning
confidence: 99%
“…Decision makers for both adults and children consent relatively equally and the depth and detail of the donation discussion is associated with higher consent rates. 30 Consent rates in Europe, North America, the UK and Australia for both adults and children range from 42 to 69%. 7,29,[31][32][33][34][35] In Australia, the rate is similar for adult (52.8%) 33 and paediatric (50%) patients.…”
Section: Consentmentioning
confidence: 99%
“…A recent analysis of potential brain‐dead eligible donors found that family authorization rates for deceased organ donation following an eligible death varied significantly between DSAs, resulting in a loss of >5700 transplantable organs during a 5‐ear period . A large body of research demonstrates the critical importance of communication to family authorization of donation . This report examines the communication processes and outcomes in requests for solid organ donation made by OPO staff in 8 of the 11 OPTN regions.…”
Section: Introductionmentioning
confidence: 99%